ADHM Wilson line defect indices - Hirotaka Hayashi; Tomoki Nosaka; Tadashi Okazaki (Journal of High Energy Physics)
Abstract The Coulomb and Higgs indices of the 3d N $$ \mathcal{N} $$ = 4 U(N) ADHM theories can be decorated by line defect operators as the line defect correlators. We obtain exact closed-form expressions and various non-trivial algebraic relations for the correlators of the Wilson lines in the fundamental and (anti)symmetric representations by means of the Hall-Littlewood expansion, the Fermi-gas method and the residue calculation. From the large N limit of the correlators we obtain the single particle gravity indices which are expected to encode the spectra of fluctuation modes on the gravity duals of line operators in M2-brane SCFTs.